Desarrollar la aplicación web para la gestión administrativa del Tecnicentro Don Hugo y sus sucursales, ubicado en la ciudad de Guayaquil - Olivo Piza, Merlin Lilian (2015)
The current project was carried out with the use of the latest technology and tools that make it easy to create web applications quickly and safely. which developed the Web application for the Administrative Management Company SA Tecnicentro Don Hugo and its branches, it serve for a better control and good management in the course of business, also will optimize administrative processes and facilitate the use of information securely, to ensure the availability of highly reliable information to greatly reduce costs to the company and help protect the environment by preventing the inappropriate use of paper. To achieve the goal, the RAD (Rapid Application Development). Methodology has been implemented. RAD is one of the most agile methodologies used in the media and to define the reach and purpose the “IEEE830” standards applied as a starting point in structuring the project. Regarding the technology used we Visual Studio 2013, an IDE tools including CASE and has everything you need for a safe and friendly application interfaces. In the database it was used in the same owns the latest version of Microsoft SQL Server 2012 ensures reliable data repository with a clean and robust architecture. HTML5 code being the best option for compatibility with browsers when going into production application was used in web programming. After reaching our goal the web application will work more consistent management, optimization and efficiency in control processes preventing the company incur expenses for logistics in the recovery of physical documents is what is done today.